2022
DOI: 10.1021/acsami.1c23622
|View full text |Cite
|
Sign up to set email alerts
|

Large Room-Temperature Electrocaloric Response Realized in Potassium-Sodium Niobate by a Relaxor Enhancement Effect and Multilayer Ceramic Construct

Abstract: The development of high-performance electrocaloric (EC) materials is crucial for solid-state refrigeration applied in micro-electromechanical systems. Herein, a large room-temperature EC response is realized in (1 – x)­(K0.49Na0.49Li0.02)­(Nb0.8Ta0.2)­O3–xCaZrO3 (KNLNT–xCZ) benefiting from a relaxor enhancement effect and multilayer ceramic construct. The relaxor enhancement effect is because the long-range order is broken by adding CaZrO3, which is in favor of enhancing the temperature change (ΔT) and broaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…(c) Evolution of O distortion with increasing temperature and the temperature dependence of E C , E AF , and E FA for the NN-0.02CZ ceramic. (d) Comparison of EC performance (Δ T vs T span ) of AFE and FE ceramics (NN-based, ,,, BaTiO 3 -based, ,, Na 0.5 Bi 0.5 TiO 3 -based, , (K, Na)­NbO 3 -based, , and lead-based ).…”
Section: Resultsmentioning
confidence: 99%
“…(c) Evolution of O distortion with increasing temperature and the temperature dependence of E C , E AF , and E FA for the NN-0.02CZ ceramic. (d) Comparison of EC performance (Δ T vs T span ) of AFE and FE ceramics (NN-based, ,,, BaTiO 3 -based, ,, Na 0.5 Bi 0.5 TiO 3 -based, , (K, Na)­NbO 3 -based, , and lead-based ).…”
Section: Resultsmentioning
confidence: 99%
“…To be practical for cooling applications, EC materials should exhibit a large adiabatic Δ T and low working temperature near room temperature. In ferroelectrics, relaxor ferroelectrics (RFEs) exhibit a high EC response at room temperature and a broad T span due to polar nanoregions . Poly­(vinylidene fluoride) (PVDF)-based copolymers and terpolymers are a type of organic RFEs that have undergone significant improvements since their initial discovery.…”
Section: Introductionmentioning
confidence: 99%
“…In ferroelectrics, relaxor ferroelectrics (RFEs) exhibit a high EC response at room temperature and a broad T span due to polar nanoregions. 7 Currently, the EC effect is mostly used in cooling devices that require external action mechanisms to assist in heat transfer, with little focus on heating processes. 9,10 In addition to temperature management, EC materials can find use as driving elements in thermal-driven soft actuators.…”
Section: Introductionmentioning
confidence: 99%
“…ECE research received a tremendous boost after a giant ∆T of 12 K was reported in inorganic Pb(Zr 0.95 Ti 0.05 )O 3 and poly(vinylidene fluoride-co-trifluoroethylene) copolymer thin films [8,9]. ECE in relaxor ferroelectrics (FEs) [10][11][12][13][14][15], antiferroelectrics (AFEs) [16][17][18], polymers [19][20][21][22][23], polymer-ceramic composites [24][25][26] and multilayer capacitors [27][28][29][30] were soon explored. Also, electrocaloric (EC) prototype devices were developed [31][32][33][34][35] and great progress has been made in EC phase-field models [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%